Understanding the metabolic perturbations in Carica papaya Linn. due to different ripening practices/agents using gas chromatography‐mass spectrometry based metabolomics. Issue 3 (16th July 2020) - Ganneru, Sireesha; Shaik, Hussain; Peddi, Kiranmayi; Mudiam, Mohana Krishna Reddy
Abstract: The study of fruit‐ripening mechanism is vital as it plays a key role in the maintenance of fruit quality. Use of various xenobiotics for quick ripening has been shown to impact the quality of fruit, which in turn affect human health. In the present study, we made an attempt to understand the metabolic perturbations in Carica papaya Linn. (papaya), which has been ripened either by the ripening practice (room temperature process as control) and/or ripening agents (calcium carbide and ethylene) using gas chromatography‐mass spectrometry (GC‐MS) based metabolomics. The partial least squares‐discriminant analysis has revealed significant alternations in 13 metabolites mainly sugars, amino acids, fatty acids, and organic acids as well as disturbances in five metabolic pathways due to different ripening practice/agents. The individual comparison of calcium carbide with control and ethylene with control has found 13 and 11 metabolites, respectively, which are common to the PLS‐DA of three ripening groups. The GC‐MS–based metabolomics has been able to predict the metabolic perturbations in papaya resulting from the ripening practice/agents. The findings from the present analysis has a wide application in food quality and will help to address safety concerns.